Electrochemical oxidation of 4-chlorophenol for wastewater treatment using highly active UV treated TiO2 nanotubes. (October 2018) - Tian, Min; Thind, Sapanbir S.; Dondapati, Jesse S.; Li, Xinyong; Chen, Aicheng
Abstract: In the present work, we report on a facile UV treatment approach for enhancing the electrocatalytic activity of TiO2 nanotubes. The TiO2 nanotubes were prepared using an anodization oxidation method by applying a voltage of 40 V for 8 h in a DMSO + 2% HF solution, and further treated under UV light irradiation. Compared with Pt and untreated TiO2 nanotubes, the UV treated electrode exhibited a superior electrocatalytic activity toward the oxidation of 4-chlorophenol (4-ClPh). The effects of current density and temperature on the electrochemical oxidation of the 4-ClPh were also systematically investigated. The high electrocatalytic activity of the UV treated TiO2 nanotubes was further confirmed by the electrochemical oxidation of other persistent organic pollutants including phenol, 2-, 3-, 4-nitrophenol, and 4-aminophenol. The total organic carbon (TOC) analysis revealed that over 90% 4-ClPh was removed when the UV treated TiO2 electrode was employed and the rate constant was 16 times faster than that of the untreated TiO2 electrode; whereas only 60% 4-ClPh was eliminated at the Pt electrode under the same conditions. This dramatically improved electrocatalytic activity might be attributed to the enhanced donor density, conductivity, and high overpotential for oxygen evolution. Our results demonstrated that the application of the UV treatment to the TiO2 nanotubes enhanced their electrochemical activity and energy consumption efficiency significantly, which is highly desirable for the abatement of persistent organic pollutants. Graphical abstract: Image 1 Highlights: Direct growth of TiO2 nanotubes on Ti substrate using anodization. Substantial enhancement of TiO2 electrocatalytic activity using facile UV treatment. Superior activity toward the electrochemical oxidation of 4-chlorophenol. 16 and 5 times higher catalytic activity than the untreated TiO2 and Pt electrodes, respectively.